Geology of La Reforma caldera complex, Baja California, Mexico. Issue 2 (3rd July 2019) - García Sánchez, L.; Macías, J.L.; Sulpizio, R.; Osorio-Ocampo, L.S.; Pellicioli, C.; Pola, A.; Avellan, D.R.; Cisneros, G.; García, F.; Ocampo-Díaz, Y.Z.E.; Lira-Beltran, R.M.; Saucedo, R.; et al.
ABSTRACT: A new geological map at 1:50, 000 scale of La Reforma Caldera Complex has been produced applying modern survey methodologies to volcanic areas. This map aims to represent a reliable and objective tool to understand the geological evolution of the region. La Reforma Caldera Complex is a Pleistocene nested caldera located in the central part of the Baja California peninsula, Mexico. The twelve formations defined within the Quaternary volcanic record were grouped into three phases (pre-caldera, caldera, and post-caldera). The pre-caldera phase (>1.35 Ma) is characterized by scattered eruptions, mostly occurred in submarine environment. The caldera phase (1.35–0.96 Ma) groups several distinct explosive and effusive eruptions that formed the present-day caldera depression. The post caldera phase includes scattered effusive eruptions (ended at 0.28 Ma) and resurgence, characterized by several hundred meters of uplift of the central block within the caldera depression.